CONSTRUCTION OF EDUCATIONAL VIDEOS ON THE USE OF ONLINE QUESTIONNAIRE IN RESEARCH WITH HUMAN BEINGS (Citizenship in Action: Extension and Culture Magazine, 2023)
This study describes the process of creating of three educational videos on the use of online questionnaires in research with human beings. This study was carried out in the context of a Research Ethics Committee as a way of developing instructions for researchers who intend to use online questionnaires as an instrument of data collection in research with human beings. Initially, an introduction was made about research ethics and the questionnaire as a research tool. The video creation process was developed using action research methodology, as proposed by Michel Thiollent, with a group of members of a research ethics committee. The research respected the action-research cycle, fulfilling the stages of problem identification, planning, action, description and evaluation. The problem identified was the lack of guidelines for the use of an online questionnaire. The preparation of the video was structured in stages, which are the preparation and approval of the script, recording and editing of the video and evaluation of the video by the research participants, these stages being carried out in the planning, action and evaluation phases respectively. The first video presents research ethics and the CEP-CONEP system; the second video addresses the consent/assent process; and the third video, guides the preparation of an online questionnaire with the registration of consent/assent. The results showed that the videos have adequacy as to the proposed objective, form and content, and sufficient aptitude to be used, pointing a way for new educational productions regarding research ethics in the future.
Keywords: research ethics; online questionnaire; educational video; action research